Like a pro: dinâmicas sociais no e-sport - MACEDO, Tarcízio Pereira (Universidade Federal do Pará, 2018)
Starting from an understanding of the social coming from the simmelian work, this research seeks to understand the social dynamics of a team of semiprofessional players of the Multiplayer Online Battle Arena (MOBA) League of Legends (League or LoL) in the local competitive community of Belém, in the Pará. Through a micro-sociological approach, the objective is to understand the process of formation and maintenance of the social fabric among players who engage in the organized competitive digital game, also known as electronic sport (e-sport) or pro gaming. This study specifically focuses on understanding how group dynamics between players and teams is manifested in this particular competitive context, of how the social fabric is created and developed at the core of that group by trying to understand how it constitutes a variety of nuances in social dynamics, inserting more specifically in communication, camaraderie and team organization. In order to do so, based on an ethnographic study carried out with a team from the city, a theoretical framework based on a multidisciplinary theoretical matrix is developed, engendering elements of the fields of Communication Studies, Game Studies, sports and social sciences, articulating these through an anthropological and sociological sensibility. In general terms, it is concluded that the path to competitive career progression for professionals is strongly dependent on an active process of socialization between players and teams in a professional identification resulting from a whole series of actors and forces. In addition, the research demonstrates that although a functional bias is responsible for stimulating the formation of the social fabric in most teams of the local scenario, there is a particular social experience of growing relevance, an ethos of camaraderie created both among players in a team, as well as between teams, that operates as a powerful vector either for the maintenance of the social fabric or for an instrumental/functional end - of the competitive progression - facing the challenges towards professionalization. The period of coexistence, observation and contact with the interlocutors dates from June 2016 to February 2018.